Implementasi Kebijakan Penyiangan Koleksi Berdasarkan Standar Nasional Perpustakaan (SNP) No 13 Tahun 2017 di UPT Perpustakaan Universitas Negeri Makassar - Mawahda, Ainul Nurul; Marni; Nasrullah; Tawakkal (Literatify: Trends in Library Developments, 2025)
Collection weeding is very important to be done in the library. This study aims to analyze the implementation of the collection weeding policy based on the National Library Standards, at the Library Unit Makassar State University. The Problem raised are how the collection weeding policy is at the Library Unit, Makassar State University, how is the suitability of the collection weeding based on the National Library Standards, and what obstacles are experienced by librarians in carrying out collection weeding. The research method used is qualitative descriptive research. Data collection was carried out through interviews, with three informants, namely librarians, observation and documentation. Data analysis and processing techniques, data use, data reduction, data presentation and drawing conclusions. The results of this study indicate that librarians have implemented a collections weeding policy and implemented it, with the considerations taken, namely, the selection process and withdrawal of collections from those that are considered no longer useful for display. In accordance with the National Library Standards, the Library Unit, Makassar State University has carried out collection weeding once a year, and made the library more effective. And the obstacles funding and lack SDM.